The effect of nitrogen pressure on cathodic arc deposited NbN thin films - Cansever, N.; Danisman, M.; Kazmanli, K. (ELSEVIER SCIENCE SA, 2008)
NbN thin films were deposited on non-standard grade high speed steel (HSS) (79.90 wt.% Fe, 0.71 wt.% C, 6.09 wt.% W, 4.52 wt.% Mo, 3.95 wt.% Cr, 1.82 wt.% Co, 1.75 wt.% V and a hardness of 65 HRC) using cathodic arc deposition at 0.125, 0.5, 1.0 and 1.5 Pa nitrogen pressures (P-N2), with a bias voltage of -150 V. X-ray diffraction (XRD), Scanning Electron Microscope (SEM), Nanoindentation and Rockwell C analysis were used to characterize the thin films in order to identify the NbN phases and to investigate the influence of P-N2 on mechanical properties. Hexagonal beta-Nb2N, epsilon-NbN and delta'-NbN0.95 are identified in XRD analysis. Hardness values derived by nanoindentation technique are 20 GPa for beta-Nb2N, epsilon-NbN and 40 GPa for delta'-NbN0.95. Due to the complexity of phase system special attention was focused on identification of NbN phases by deconvolating the XRD peaks especially at 0.5 Pa in which both epsilon-NbN and beta-Nb2N were found. Rockwell C analysis revealed that the him adhesion is found to be poor at lower P-N2, due to the brittle nature of beta-Nb2N. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: NbN thin films; Cathodic arc deposition; XRD; Nanoindentation; Deconvolation; TIN/NBN SUPERLATTICE COATINGS; MAGNETRON SPUTTER-DEPOSITION; BEAM-ASSISTED DEPOSITION; NIOBIUM NITRIDE COATINGS; MECHANICAL-PROPERTIES; SUPERCONDUCTING NIOBIUM; MULTILAYER COATINGS; DIFFRACTION DATA; VACUUM; Materials Science; Physics